Pengaruh E-Service Quality Terhadap E-Customer Satisfaction Dan Dampaknya Terhadap E-Customer Loyalty: Studi Pada Pengguna Aplikasi BRImo Mahasiswa Aktif Program Studi S1 Manajemen UPN “Veteran” Yogyakarta - Aprilia Luluk Latifah; Tri Wahyuningsih (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to examine and analyze the effect of the dimensions on e-service quality owned by the BRImo application on e-customer satisfaction and to determine the impact of the influence of e-customer satisfaction on e-customer loyalty of BRImo application users. The population in this study were active students of the BRImo Application Users of the UPN “Veteran” Yogyakarta Undergraduate Management Study Program. The sampling technique used purposive sampling. Data was obtained by distributing questionnaires using Google forms, and the number of respondents obtained was 100 respondents. This study uses descriptive analysis techniques and SEM techniques with the help of SmartPLS. The results of this study indicate that all dimensions of e-service quality which include site organization, reliability, responsiveness, user friendliness, personal need, and efficiency have a positive and significant effect on e-customer satisfaction for users of the BRImo Application Active Student Undergraduate Management Study Program UPN